Chemical analyses of manganese nodule samples from the ESSA-NOAA AMC-11-67 cruise over the Blake Plateau - Wittkopp, R W; Stephens, J D (PANGAEA, 2023)
For assessing their desulfuration and mineral potential, manganese rich concretions were selected from the stations of the AMC-11-67 cruise performed by ESSA (NOAA) in October 1967 and analysed by the Kennecott Copper Corporation.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment